Nursing management of a rheumatoid arthritis patient treated by wax therapy with Chinese herbal medicine (中药蜡疗治疗类风湿关节炎1例护理体会) - LU Lin (芦琳); TANG Ling (唐玲); LI Ye (李野); LI Suqian (李苏茜) (Association of Integrative Nursing, 2021)
This paper summarized the nursing measures for a rheumatoid arthritis patient treated by wax therapy with Chinese herbal medicine. Key issues of nursing included preparation of Chinese herbal medicine and wax, procedure and cautions of wax therapy, life care, dietary intervention, psychological intervention. The wax therapy was conducted based on the syndrome differentiation and prescription selection, and coordinate nursing interventions were carried out to relieve patient's pain and improve the activity of daily. The wax therapy with Chinese herbal medicine has advantages of easy-to-use, few adverse reactions, low cost and high acceptance among patients. (本文总结中药蜡疗治疗1例类风湿关节炎患者的护理经验, 主要包括中药膏以及蜡块的制作、蜡疗操作方法、注意事项以及生活指导、饮食调护、心理干预等护理配合。通过辨证分型, 选取针对性药方和穴位, 同时配合相关护理, 能有效缓类风湿关节炎痹患者疼痛症状, 提高其日常生活能力, 且中药蜡疗技术操作简单、不良反应少、成本低, 患者也更易于接受。)